Building Collaborative Evidence-Based Frameworks for Criminal Justice Policy - Brancale, Julie (Criminal justice policy review, 2021)
Researcher–policymaker/practitioner partnerships (RPPs) have emerged as a successful tool for translating research into policy and practice. However, the available research has focused on RPPs with law enforcement and correctional agencies. Notably absent are studies that describe and evaluate RPPs between researchers and legislative bodies. Specifically, questions remain about the establishment, unique constraints, best practices for effective implementation, and sustainability of partnerships between researchers and policymakers. This study contributes to the literature by describing a unique RPP between a university and a state legislature. Through this retrospective case analysis, we describe the steps taken to initiate the partnership, its implementation, and outcomes. Importantly, in the context of the prior research, we describe the lessons learned, next steps, and implications for partnerships with policymakers.